Rapid identification of paragonimiasis foci by lay informants in Lao People's Democratic Republic. - Peter Odermatt; Duong Veasna; Wei Zhang; Nanthasane Vannavong; Souraxay Phrommala; Shigehisa Habe; Hubert Barennes; Michel Strobel (Public Library of Science (PLoS), 2009)
Background Paragonimiasis is a food-borne trematodiasis leading to lung disease. Worldwide, an estimated 21 million people are infected. Foci of ongoing transmission remain often unnoticed. We evaluated a simple questionnaire approach using lay-informants at the village level to identify paragonimiasis foci and suspected paragonimiasis cases. Methodology/principal findings The study was carried out in an endemic area of Lao People's Democratic Republic. Leaders of 49 remote villages in northern Vientiane Province were asked to notify suspected paragonimiasis patients using a four-item questionnaire sent through administrative channels: persons responding positively for having chronic cough (more than 3 weeks) and/or blood in sputum with or without fever. We validated the village leaders' reports in ten representative villages with a door-to-door survey. We examined three sputa of suspected patients for the presence of Paragonimus eggs and acid fast bacilli. 91.8% of village leaders participated and notified a total of 220 suspected patients; 76.2% were eventually confirmed; an additional 138 suspected cases were found in the survey. Sensitivity of village leaders' notice for "chronic cough" and "blood in sputum" was 100%; "blood in sputum" alone reached a sensitivity of 85.7%. Significance Our approach led to the identification of three previously unknown foci of transmission. A rapid and simple lay-informant questionnaire approach is a promising low-cost community diagnostic tool of paragonimiasis control programs.